MODERN INFORMATION AND COMMUNICATION TECHNOLOGIES IN THE PROCESS OF TEACHING RUSSIAN AS A FOREIGN LANGUAGE - Namaz Mamasalievich Karimov; Zulfiya Оdiljanovna Karimova (Bright Mind Publishing, 2025)
The article deals with the issue of introducing information and communication technologies in the educational process of teaching Russian as a foreign language with a focus on the combination of traditional and innovative methods. Innovative approaches including multimedia, cloud technologies and distance learning are analysed.
Keywords: Information and communication technologies (ICT), learning process, Russian as a foreign language (RFL), tools, innovative methods.